Axial length and IOL power stability in macular edema treated with anti-VEGF: a preliminary study using OLCR biometry - Mehmet Omer Kiristioglu; Selim Doganay; Gamze Ucan Gunduz (BMC Ophthalmology)
Abstract Purpose To investigate axial length (AxL) variability and intraocular lens (IOL) power stability in macular edema (ME) patients undergoing intravitreal anti-VEGF therapy using Lenstar biometry. Methods In this preliminary observational study, 32 patients (64 eyes) with unilateral macular edema (ME) due to diabetic retinopathy or retinal vein occlusion were evaluated. AxL and IOL power were measured pre- and post-treatment using LenStar OLCR biometry. Three measurement strategies were employed: automated (AxLα), manually adjusted (AxLβ), and CRT-corrected (AxLγ). Four experienced ophthalmologists manually repositioned A-scan markers. Fellow eyes were assessed longitudinally. Statistical analyses included paired t-tests, intraclass correlation coefficients, and correlation tests. Results The mean patient age was 61.38 ± 9.44 years. Anti-VEGF treatment significantly reduced mean CRT from 444.47 ± 121.16 μm to 374.50 ± 98.90 μm (p < 0.001). The mean preoperative and postoperative AxL were 23.11 ± 0.72 mm and 23.10 ± 0.72 mm, respectively (p = 0.091), showing no significant change. However, in cases with CRT > 300 μm, AxL reduction was statistically significant (p = 0.044), though IOL power calculations remained stable (p = 0.401). Interobserver agreement was high for AxL and IOL power measurements, with intraclass correlation coefficients of 0.854 preoperatively and 0.989 postoperatively. Manual adjustments resulted in significant AxL differences between pre- and post-treatment periods (p < 0.001), while automated Lenstar measurements remained consistent. Fellow eyes IOL and AxL remained identical in both preoperative and postoperative sessions (p = 0.323 for IOL and p = 0.287 for AxL). Conclusion This preliminary observational study suggests that AxL and IOL power measurements remain stable following anti-VEGF therapy in most ME cases. Small but consistent AxL changes in eyes with high CRT may indicate a structural threshold for biometric variability. OLCR-based biometry remains reliable in real-world practice.